Combined Au/Ag nanoparticle creation in ZnO nanopillars by ion implantation for optical response modulation and photocatalysis - Mackova, A; Jagerova, A; Lalik, O; Miksova, R; Poustka, D; Mistrík, Jan; Holy, V; Schutter, J. D; Kentsch, U; Marvan, P; Azarov, A; Galeckas, A (Elsevier Science BV, 2023)
ZnO nanopillars were implanted with Au-400 keV and Ag-252 keV ions with ion fluences from 1 x 1015 cm-2 to 1 x 1016 cm-2. We compared ZnO nanopillars solely implanted with Au-ions and dually-implanted with Au and Ag-ions. Rutherford Back-Scattering spectrometry (RBS) confirmed Ag and Au embedded in ZnO nanopillar layers in a reasonable agreement with theoretical calculations. A decreasing thickness of the ZnO nanopillar layer was evidenced with the increasing ion implantation fluences. Spectroscopic Ellipsometry (SE) showed a decrease of refractive index in the nanopillar parts with embedded Au, Ag-ions. XRD discovered vertical domain size decreasing with the proceeding radiation damage accumulated in ZnO nanopillars which effect was preferably ascribed to Au-ions. SE and diffuse reflectance spectroscopy (DRS) showed optical activity of the created nanoparticles at wavelength range 500 - 600 nm and 430 - 700 nm for the Au-implanted and Au, Ag-implanted ZnO nanopillars, respectively. Photoluminescence (PL) features linked to ZnO deep level emission appear sub-stantially enhanced due to plasmonic interaction with metal nanoparticles created by Ag, Au-implantation. Photocatalytic activity seems to be more influenced by the nanoparticles presented in the layer rather than the surface morphology. Dual implantation with Ag, Au-ions enhanced optical activity to a larger extent without significant morphology deterioration as compared to the solely Au-ion implanted nanopillars.
Kombinovaná tvorba nanočástic Au/Ag v ZnO nanopilířích pomocí implantace iontů pro modulaci optické odezvy a fotokatalýzu
Keywords: ZnO nanopillars; Au; Ag nanoparticles ion implantation; SPR; doped ZnO nanostructures; ZnO nanopilíře; Iontová implantace; Au a Ag nanočástice; SPR; dopované nanostruktury; ZnO